Self-gravitating solutions in Yang–Mills–Chern–Simons theory coupled to 3D massive gravity - Cristóbal Corral; Daniel Flores-Alfonso; Gastón Giribet; Julio Oliva (European Physical Journal C: Particles and Fields)
Abstract We study self-gravitating solutions of three-dimensional massive gravity coupled to the Yang–Mills–Chern–Simons gauge theory. Among these, there is a family of asymptotically Warped-Anti de Sitter black holes that come to generalize previous solutions found in the literature and studied in the context of WAdS $$_3$$ 3 /CFT $$_2$$ 2 . We also present self-gravitating solutions to three-dimensional Einstein–Yang–Mills theory, as well other self-gravitating solutions in the presence of higher-curvature terms.